2012
DOI: 10.1111/j.1757-1707.2012.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization increases diversity and productivity of prairie communities used for bioenergy

Abstract: Using prairie biomass as a renewable source of energy may constitute an important opportunity to improve the environmental sustainability of managed land. To date, assessments of the feasibility of using prairies for bioenergy production have focused on marginal areas with low yield potential. Growing prairies on more fertile soil or with moderate levels of fertilization may be an effective means of increasing yields, but increased fertility often reduces plant community diversity. At a fertile site in central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 41 publications
5
70
1
3
Order By: Relevance
“…4). As will be noted in the following sections, this effect is associated with lower soil T soil when prairies received N fertilization and stimulated fuller plant canopies ( Jarchow and Liebman, 2013). Additionally, Jarchow and Liebman (2013) reported that the fertilized and unfertilized prairies at the same field sites were dominated by native C 3 and C 4 plants, respectively.…”
Section: Soil-surface Carbon Dioxide Effluxesmentioning
confidence: 96%
See 3 more Smart Citations
“…4). As will be noted in the following sections, this effect is associated with lower soil T soil when prairies received N fertilization and stimulated fuller plant canopies ( Jarchow and Liebman, 2013). Additionally, Jarchow and Liebman (2013) reported that the fertilized and unfertilized prairies at the same field sites were dominated by native C 3 and C 4 plants, respectively.…”
Section: Soil-surface Carbon Dioxide Effluxesmentioning
confidence: 96%
“…As will be noted in the following sections, this effect is associated with lower soil T soil when prairies received N fertilization and stimulated fuller plant canopies ( Jarchow and Liebman, 2013). Additionally, Jarchow and Liebman (2013) reported that the fertilized and unfertilized prairies at the same field sites were dominated by native C 3 and C 4 plants, respectively. They also reported that fertilized prairies had greater diversity of plant species in August, whereas unfertilized prairies had greater diversity in June ( Jarchow and Liebman, 2013).…”
Section: Soil-surface Carbon Dioxide Effluxesmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, Rothrock and Squiers (2003) found that N fertilized prairie communities remained dominated by annual weeds and did not shift to perennial species. Alternatively, Jarchow and Liebman (2012) found that spring fertilization of prairies increased late season prairie species diversity and did not encourage exotic species.…”
mentioning
confidence: 99%